Emerging Trends in Gel Nail Allergies: Prevalence, Symptoms, and Occupational Hazards Associated with Acrylate Sensitization - Patryk Zembala; Julita Zembala; Roksana Zembala; Dominik Adamowicz; Ewa Gacoń; Inga Łopuszyńska (Kazimierz Wielki University, 2023)
Introduction and objective Gel nail allergies have become a growing concern in recent years, as individuals experience adverse immune reactions to the chemicals present in gel nail products. The popularity of gel nails, known for their long-lasting and durable finish compared to traditional nail polishes, has increased in the beauty industry. However, specific constituents, particularly acrylate compounds used in gel nail formulations, can trigger allergic responses in susceptible individuals. Abbreviated description of the state of knowledge Findings from the reviewed articles indicate that allergic reactions to acrylates in gel nail products can manifest in various ways, including contact dermatitis, dermatoses, and general allergic responses. Nail technicians, due to their frequent exposure to gel nail products and other potential allergens, are particularly vulnerable to occupational hazards associated with acrylate sensitization. These insights highlight the need for preventive measures to protect the health and well-being of nail technicians and promote a safer working environment. Summary This literature review addresses the emerging issue of gel nail allergies and provides valuable information regarding the prevalence and characteristics of allergic reactions to acrylates. The article underscores the significance of increasing awareness, implementing preventive measures, and effectively managing gel nail allergies. By doing so, the beauty industry can ensure a safer approach to gel nail applications, benefitting both nail technicians and consumers alike.